MTA1, a transcriptional activator of breast cancer amplified sequence 3 - Gururaj, Anupama E. (National Academy of Sciences, 2006)
Here we define a function of metastasis-associated protein 1 (MTA1), a presumed corepressor of estrogen receptor α (ERα), as a transcriptional activator of Breast Cancer Amplified Sequence 3 (BCAS3), a gene amplified and overexpressed in breast cancers. We identified BCAS3 as a MTA1 chromatin target in a functional genomic screen. MTA1 stimulation of BCAS3 transcription required ERα and involved a functional ERE half-site in BCAS3. Furthermore, we discovered that MTA1 is acetylated on lysine 626, and that this acetylation is necessary for a productive transcriptional recruitment of RNA polymerase II complex to the BCAS3 enhancer sequence. BCAS3 expression was elevated in mammary tumors from MTA1 transgenic mice and 60% of the human breast tumors, and correlated with the coexpression of MTA1 as well as with tumor grade and proliferation of primary breast tumor samples. These findings reveal a previously unrecognized function of MTA1 in stimulating BCAS3 expression and suggest an important role for MTA1-BCAS3 pathway in promoting cancerous phenotypes in breast tumor cells.